2013 IEEE Workshop on Applications of Computer Vision (WACV) 2013
DOI: 10.1109/wacv.2013.6475038
|View full text |Cite
|
Sign up to set email alerts
|

Video event recognition using concept attributes

Abstract: We propose to use action, scene and object concepts as semantic attributes for classification of video events in InTheWild content, such as YouTube videos. We model events using a variety of complementary semantic attribute features developed in a semantic concept space. Our contribution is to systematically demonstrate the advantages of this concept-based event representation (CBER) in applications of video event classification and understanding. Specifically, CBER has better generalization capability, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 32 publications
0
73
0
Order By: Relevance
“…The first phase is video analysis and in this phase we adopted a Concept-Based Event Recognition (CBER) approach to video event classification similar to Ref. 5. We modeled events in a semantic space consisting of concepts related to actions, scenes and objects.…”
Section: Proposed Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first phase is video analysis and in this phase we adopted a Concept-Based Event Recognition (CBER) approach to video event classification similar to Ref. 5. We modeled events in a semantic space consisting of concepts related to actions, scenes and objects.…”
Section: Proposed Solutionmentioning
confidence: 99%
“…However, unlike Ref. 5 we used Spatio-Temporal Interest Points Chain (STIPC) for detection of action concepts and chisquare ( 2 χ ) radial basis function (RBF) kernel for SVM learning. In the second phase which is crime prediction, we developed a neuro-fuzzy inference system for computing crime imminence levels across our simulated study area.…”
Section: Proposed Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [4], a multimedia event recounting method is proposed based on detected concepts in order to build discriminative event models using a SVM. Similar work is carried out in [5] aiming at video event classification using semantic concept attributes of different categories like action, scene, object, etc. [6] employed an intermediate representation of semantic model vectors trained from SVMs as a basis for detecting complex events, and revealed that this representation outperforms -and is complementary to -other low-level visual descriptors for event modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the local neighbourhood structure is preserved by consider- Human language is the predominant means of communication. The utilisation of human language models in computer vision problems such as scene understanding [80], image or video description [58] could help in transferring knowledge acquired by human experts for solving these problems.…”
Section: Unsupervised Automatic Attribute Discovery Methods Via Multi-mentioning
confidence: 99%